Comparative transcriptome analysis between inbred lines and hybrids provides molecular insights into K+ content heterosis of tobacco (Nicotiana tabacum L.) - Mo, Zejun; Luo, Wen; Pi, Kai; Duan, Lili; Wang, Pingsong; Ke, Yuzhou; Zeng, Shuaibo; Jia, Rongli; Liang, Ting; Huang, Ying; Liu, Renxiang (Frontiers in Plant Science, 2022)
Potassium (K+) is essential for crop growth. Increasing the K+ content can often directly promote the improvement of crop yield and quality. Heterosis plays an important role in genetic improvement and leads to genetic gains. We found that the K+ content of tobacco showed significant heterosis, which is highly significant for cultivating tobacco varieties with high K+ content. However, the mechanism by which K+ content heterosis occurs in tobacco leaves is not clear. In this study, a comprehensive comparative transcriptome sequencing analysis of root samples from the hybrid G70×GDH11 and its parental inbred lines G70 and GDH11 was performed to elucidate the importance of the root uptake capacity of K+ in the formation of heterosis. The results showed that 29.53% and 60.49% of the differentially expressed genes (DEGs) exhibited dominant and over-dominant expression patterns, respectively. These non-additive upregulated DEGs were significantly enriched in GO terms, such as metal ion transport and reaction, ion balance and homeostasis, ion channel activity, root meristem growth, and regulation of root hairs. The KEGG annotation results indicated that these genes were mainly involved in the pathways such as energy metabolism, carbohydrate formation, amino acid metabolism, and signal transduction. Further analysis showed that probable potassium transporter 17 (NtKT17) and potassium transporter 5-like (NtKT5), associated with potassium ion absorption, glutamate receptor 2.2-like and glutamate receptor 2.8-like, associated with ion channel activity, and LOC107782957, protein detoxification 42-like, and probable glutamate carboxypeptidase 2, associated with root configuration, showed a significantly higher expression in the hybrids. These results indicated that the overdominance of DEGs played a key role in the heterosis of K+ content in tobacco leaves, and the overexpression of the genes related to K+ uptake, transport, and root development in hybrids helped to improve the K+ content of plants, thus showing the phenomenon of heterosis.